Trade-off between fitness and experience: insights from historical data on ODI cricket - Vipra Jain; Subrato Banerjee; Subrato Banerjee; Priyanka Kothari (Frontiers in Behavioral Economics, 2024)
A healthy mix of younger and senior players is often desirable for any team involved in a sports-tournament. It is often argued that the experience of senior players and fitness of the younger players could complement each other. How an athlete performs is determined by the accumulation of experience that grows with age and physical fitness that declines with age. Therefore, fitness and experience are competing forces that move in opposite directions. We explore the age-range of peak-performance in the lifetime of a sportsperson where the marginal benefits from experience and fitness are on balance. Using a unique data-set of all one-day international (ODI) cricket matches played from 1971 to 2000, we find that there is an inverted U-shaped performance-age curve where performance first gets better with age, then reaches a peak before finally declining (when experience can no longer undo the effects of declining fitness). This peak-performance is attained for bowlers at around 22–26 years and for batters at about 27–30 years. These results remain robust to different specifications and controls. We employ a theoretical framework for policy analyses of actual selection decisions made during our period of study. These analyses build on the empirical section of our paper.